AST, ALT, Bilirubin and AST/ALT Ratio role; Covid- 19 Patients - Mohammad Nazri, Nor Amirah; Wan Azman, Wan Norlina; Musa, Norsyuhadah; Tuan Ismail, Tuan Salwani; Harun, Azian; Yaacob, Najib Majdi; Sulong, Sarina; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Che Mat, Mahaya; Zulkeflee, Hani Ajrina (2022)
Background Impaired liver function upon admission has been linked to the severity of COVID-19 infection, yet the data is debated [1]. Therefore, this retrospective study aimed to evaluate the liver function among COVID-19 patients during hospitalization and its association with the disease severity. Methodology The patient aged 18 to 80 with positive COVID-19 at Hospital Raja Perempuan Zainab II (HRPZ II), Kota Bharu, Kelantan, with available AST, ALT, Bilirubin, and AST/ALT ratio data on admission, were retrospectively evaluated from March 2021 to March 2022. Disease severity was categorized based on Annex 2e guidelines by Malaysia's Ministry of Health, which further classified them into mild to moderate disease (Stage 1-3) and severe to critical illness (Stage 4-5). The AST, ALT, Bilirubin, and AST/ALT ratio levels on Day 1 admission were archived from the electronic medical record system and compared between the two groups. The statistical analysis was using SPSS version 27. This study was approved by (JEPeM-USM) protocol code USM/JEPeM/21100691 and Ministry of Health Malaysia NMRR-21-762-58458 (IIR). Results and Discussion The study included a total of 168 COVID-19 patients with a mean (SD) age of 46.67(16.10) for mild to moderate and 56.66(12.41) for severe to critical. There is a significant age group for both groups (p-value=0.002). During hospitalization, 16(14.41%) patients progressed to death from severe to critically ill patients. Upon admission, the median (IQR) of AST and ALT were significantly higher in the severe to critical group compared to in the mild to moderate group, [AST; 39.0(49.0) and 24.0(14.0), ALT 38.0(43.0) and 21.0(18.0)], p<0.05. However, no significant difference between both groups for bilirubin level and AST/ALT ratio. Non-survivors had a higher AST and ALT level compared to survivors, with a median (IQR) of [AST 98.0(88.0) and 32.0 (26.0), ALT of 67.5(90.0) and 28.0(31.0), (p<0.05). Similarly, no significant difference between non-survivors and survivors for bilirubin and AST/ALT ratio. Our study support that, abnormal liver function at admission has been shown to be associated with the disease severity and mortality of COVID-19 infection. However, there is also a need to observe the COVID-19 survivors' hepatobiliary sequelae and dynamic liver function changes following hospital discharge. Conclusion Abnormal AST and ALT level at admission has been shown to be associated with the disease severity and mortality of COVID-19 infection. Further study needed to evaluate liver damage in COVID-19 post-discharge.